Crystallization behavior of milk fat, palm oil, palm kernel oil, and cocoa butter with and without the addition of cannabidiol. (25th November 2022) - Cooney, Joseph; Hilton, Isaac; Marsh, Melissa; Jones, Annalisa; Martini, Silvana
Abstract: The objective of this study was to evaluate the effect of cannabidiol (CBD) on the crystallization behavior and physical properties of various fats. Anhydrous milk fat (AMF), palm oil (PO), palm kernel oil (PKO), and cocoa butter (CB) were chosen for this study, for their unique crystallization behaviors. CBD was added at 1 and 2.5% wt/wt to these fats, and the crystallization behavior was evaluated at 26°C for AMF and PO and at 22°C for PKO and CB. Control samples with no CBD were prepared and evaluated as well. Results show that CBD delayed the crystallization of all fats with the least effect observed for the PO. Slight increases in crystal size were observed with the addition of CBD for all samples. CBD did not affect the melting profile of AMF or CB, but it increased the peak temperature of PO and decreased the enthalpy of PKO. Similarly, hardness was only affected by CBD in PO samples, with harder materials obtained for samples containing 2.5% CBD. The same trend was observed for elasticity. In addition, the elasticity of AMF increased with the addition of CBD but not its hardness. Overall, this study indicates that the effect of CBD on fat crystallization is highly dependent on the type of fat used. Producers of fat‐based products that are willing to include CBD in their formulations must carefully control processing conditions to ensure product quality.